PENGARUH PENDIDIKAN KESEHATAN TENTANG PENYAKIT DEMAM BERDARAH DENGUE TERHADAP PERILAKU AKTIF PENCEGAHAN PENYAKIT DEMAM BERDARAH DENGUE PADA IBU-IBU WARGA MINAPADI KELURAHAN NUSUKAN KOTA SURAKARTA - Kustini, Helmi; Betty, Faizah (Universitas Muhammadiyah Surakarta, 2008)
Background: Strive to prevent the wide-speading of disease of dengue dengue require to be conducted by a construction and make-up of role and also society in movement of Eradication of Mosquito Suggestion ( PSN) pass the health education. Target of: knowing active behavior prevention DBD of mother ats citizen Minapadi Nusukan Surakarta before and after health education.Method: this research use the device of experiment research with the form of one group pre test the and post test the design. Sampel taken by counted 33 responder coming from 3 RT, taken with claste sampling. Appliance of data collecting in this research use the fundamental method in the form of observation. Analyse the data use the different test of mean ( Paired Sample t test). Result: ( 1) There are active behavioral difference prevention DBD before and after health education. This matter is proven from result test the hypothesis with the test t obtaining value thitung accepted at level signifikansi 5%; ( 2) active Behavior prevention DBD after health education (mean score 11,636) seen higher than behavior of prevention DBD before health education (mean score 9,242); (3) Quality of active behavior prevention DBD after existence of health education show the existence of improvement behaviorally is downhill ugly category become counted 15,2%, behavior is mounting to become 60,6%, and good category mount to become 24,2%. Active behavior prevention DBD before education yield the ugly category behavior counted 27,3%, medium 57,6%, and good category only 15,2%. This matter indicate that the health education have an effect on positive to active behavior prevention DBD.Â